Tutoria entre estudantes: uma proposta de trabalho que prioriza a aprendizagem - Lourdes Maria Bragagnolo Frison (Universidade do Minho, 2012)
This article aims at analyzing tutoring, a teaching style used to enhance collaborative learning, performed through the collaboration among students. The historical development of conceptual aspects was explored and the study of tutoring on current days was established as the point of reference. Based on such theoretical support, a work of tutoring among peers was conducted with Pedagogy students of a public university. The activity was evaluated by means of a tool aiming at determining the importance of this strategy for students' performance. The analysis of the results highlighted that the work was productive. The collected data confirmed that this teaching style provided collaborative, active, interactive, mediated and self-regulated learning.